Effects of carbohydrate quantity and glycemic index on resting metabolic rate and body composition during weight loss. (November 2015) - Karl, J. Philip; Roberts, Susan B.; Schaefer, Ernst J.; Gleason, Joi A.; Fuss, Paul; Rasmussen, Helen; Saltzman, Edward; Das, Sai Krupa
Abstract : Objective: To examine the effects of diets varying in carbohydrate and glycemic index (GI) on changes in body composition, resting metabolic rate (RMR), and metabolic adaptation during and after weight loss. Methods: Adults with obesity ( n = 91) were randomized to one of four provided‐food diets for 17 weeks. Diets differed in percentage energy from carbohydrate (55% or 70%) and GI (low or high) but were matched for protein, fiber, and energy. Body weight, body composition, RMR, and metabolic adaptation (measured RMR–predicted RMR) were measured during weight loss and subsequent weight stability. Results: No effect of dietary carbohydrate content or GI on body weight loss or percentage of weight lost as fat mass (FM) was observed. Measured RMR was significantly lower (−226 kJ/day [95% CI: −314 to −138 kJ/day], P < 0.001) than predicted RMR following weight loss, but this difference was attenuated after 5 weeks of weight stability. Metabolic adaptation did not differ by dietary carbohydrate content or GI and was not associated with weight regain 12 months later. Conclusions: Moderate‐carbohydrate and low‐GI diets did not preferentially reduce FM, preserve lean mass, or attenuate metabolic adaptation during weight loss compared to high‐carbohydrate and high‐GI diets.